Fate of Poster Abstracts Presented at the 2009 American College of Surgeons Clinical Congress (Translation: The University of Toledo Journal of Medical Sciences, 2017)
Background: The American College of Surgeons (ACS) holds an annual clinical congress which provides the opportunity to present innovative research to academic and community surgeons from around the globe. The purpose of this study was to evaluate the publication rate of poster abstracts presented at the 2009 American College of Surgeons Clinical Congress to assess the factors influencing publication and determine the impact factor of these journals.Methods: All posters presented at the 2009 ACS were included in the study. A Pubmed-Medline search was performed to identify a matching journal article. Topics, country of origin, study type, study center and publication year were tabulated. Journals and impact factors of publication were noted.Results: Of the 333 poster abstracts presented, 62 (18.6%) were published as full-text articles. Two studies published well in advance of the meeting were removed. 36/60 (60%) of the published studies were from The United States. The average time to publication was 16.8 months. 51/60 (85%) of the studies were conducted in academic institutions. The average impact factor was 2.88. The median impact factor for studies originating from the United States was 3.3 (0.71-4.5). The median impact factor for international studies was 2.38 (0-7.22). This observation did not reach statistical significance (p=0.102) 8 (13.3%) of these manuscripts were published in the Journal of the American College of Surgeons (the official journal of the meeting). There were several abstract characteristics found to be associated with a higher publication rate. A higher rate was found for abstracts for randomized clinical trials, basic science studies, and university programs. The rates did not differ between author specialties.Conclusion:The publication rate for abstracts presented at the 2009 ACS clinical congress was lower than rates from other fields of medicine. Factors leading to failure to publish were non-randomized trials, non-university affiliation and single center studies. Encouraging authors to submit their presentations for full-text publication might improve the rate of publication. Authors should be wary of accepting poster abstracts as dogma; authors should refrain from citing them in publications especially if they are from outside the United States.